Deficient cMyBP-C protein expression during cardiomyocyte differentiation underlies human hypertrophic cardiomyopathy cellular phenotypes in disease specific human ES cell derived cardiomyocytes. (October 2016) - Monteiro da Rocha, Andre; Guerrero-Serna, Guadalupe; Helms, Adam; Luzod, Carly; Mironov, Sergey; Russell, Mark; Jalife, José; Day, Sharlene M.; Smith, Gary D.; Herron, Todd J.
Abstract: Aims: Mutations of cardiac sarcomere genes have been identified to cause HCM, but the molecular mechanisms that lead to cardiomyocyte hypertrophy and risk for sudden death are uncertain. The aim of this study was to examine HCM disease mechanisms at play during cardiac differentiation of human HCM specific pluripotent stem cells. Methods and results: We generated a human embryonic stem cell (hESC) line carrying a naturally occurring mutation of MYPBC3 ( c . 2905 +  1 G >  A ) to study HCM pathogenesis during cardiac differentiation. HCM-specific hESC-derived cardiomyocytes (hESC-CMs) displayed hallmark aspects of HCM including sarcomere disarray, hypertrophy and impaired calcium impulse propagation. HCM hESC-CMs presented a transient haploinsufficiency of cMyBP-C during cardiomyocyte differentiation, but by day 30 post-differentiation cMyBP-C levels were similar to control hESC-CMs. Gene transfer of full-length MYBPC3 during differentiation prevented hypertrophy, sarcomere disarray and improved calcium impulse propagation in HCM hESC-CMs. Conclusion(s): These findings point to the critical role of MYBPC3 during sarcomere assembly in cardiac myocyte differentiation and suggest developmental influences of MYBPC3 truncating mutations on the mature hypertrophic phenotype. Highlights: A human stem-cell derived cardiomyocyte model of HCM is proposed. The model recapitulates hallmarks aspects of HCM in vitro. Hallmarks include sarcomere disarray, hypertrophy and impaired calcium impulse propagation. HCM phenotype was associated to transient haploinsufficiency of cMyBPC during differentiation. Gene transfer of full-length MYBPC3 during differentiation prevented HCM phenotype.